3-Hydroxyphthalic Anhydride- Modified Rabbit Anti-PAP IgG as a Potential Bifunctional HIV-1 Entry Inhibitor - Zhang, Xuanxuan; Chen, Jinquan; Yu, Fei; Wang, Chunyan; Ren, Ruxia; Wang, Qian; Tan, Suiyi; Jiang, Shibo; Liu, Shuwen; Li, Lin (Frontiers in Microbiology, 2018)
ABSTRACT Several studies have reported that amyloid fibrils in human semen formed from a naturally occurring peptide fragment of prostatic acidic phosphatase (PAP248-286), known as semen-derived enhancer of viral infection (SEVI), could dramatically enhance human immunodeficiency virus type 1 (HIV-1) infection. Accordingly, SEVI might serve as a novel target for new antiviral drugs or microbicide candidates for the prevention of sexually transmitted HIV. Theoretically, a special anti-PAP or anti-SEVI antibody could reduce the enhancement of viral infection by blocking the binding of HIV and SEVI fibrils. Here, 3-hydroxyphthalic anhydride modified anti-PAP248-286 antibody, named HP-API, exhibited broad-spectrum and highly effective anti-HIV-1 activities on different genotypes and biotypes. By using time-of-addition, cell-cell fusion and a single-cycle HIV-1 infection assays, we demonstrated that HP-API is an HIV-1 entry/fusion inhibitor. Mechanism studies suggest that HP-API inhibit HIV-1 entry/fusion by targeting both HIV-1 gp120 envelop and CD4 receptor on the host cell specifically. It is noteworthy that HP-API abrogated the formation of SEVI fibrils and partially interfered with SEVI-mediated enhancement of HIV-1 infection. Based on these findings, HP-API could be considered a bifunctional HIV-1 entry/fusion inhibitor with high potential.